Mechanistic Study of Oxidation of Propanal by Potassium Ferricyanide Catalysed by Osmium Tetroxide in Alkaline Media - Singh, H.N.; Srivastava, O.P.; Kishor Singh, Kamal (Asian Journal of Chemistry, 2010)
The title reaction in alkaline medium shows first order dependenceeach on [Oxidandt], [Substrate] and [OH- ] in the absenceof catalyst But in the presence of catalyst, the reaction shows zeroorder with respect to oxidant and first order with respect to catalyst.